The impact of financial ratios towards profit changes - Pattiasina, Victor; Sejati, Fajar Rina; Seralurin, Yohanes Cores; Batilmurik, Ridolof Wenand; Aziz, Mutiara Austin Al (International research journal of management, IT and social sciences, 2018)
A Company will be interested in investors if its financial report is relevant and reliable. The relevance and reliable financial report can be reflected in the Asset Number and Liability Report on a Financial Position Statement (Balance Sheet). The success of a company can be measured by company ability, which is reflected in management performance. A company’s performance parameter that commonly used is profit change. Profit itself is important to the company since this will be decision basis for investors to invest in the company. Profit Change reflected in financial statements using fair value will bring benefits to market participants, as the financial statements itself reflects the real market value. This research aims to examine the influence of Current Ratio, Total Asset Turnover, Price Earnings Ratio, and Return on Asset, towards profit changes that based on fair value. Research problem discussed in this study was how CR, TATO, PER, and ROA influence profit changes of a property company, real estate, and building construction, in period 2013-2016. The study was based on fair value. The population was company property, real estate, and building construction, that have been listed in Indonesia Stock Exchange (ISE). It consisted of 63 companies. Through Purposive Sampling technique, 12 companies were selected to be examined. Data analysis was conducted through a multiple linear regression analysis. Results of multiple linear regression analysis showed that the CR, TATO, and PER had an influence towards Profit Changes, while ROA had no influence toward it.